Traditions and contradictions of sexual function definitions for Portuguese heterossexual men and women: medicalization and socially constructed gender effects - Alarcão, V.; Machado, F. L.; Giami, A. (Sexual and Relationship Therapy, 2016)
Research on how sexual changes are understood as dysfunctions versus normal change remains scarce, namely in societies where traditional gender roles persist among the growing diversity of sexual relationships and practices. This article discusses controversies on sexual function definitions through sociology of diagnosis and sexual scripting theoretical frameworks, drawing on 313 structured interviews with primary healthcare users of the Greater Lisbon area, followed by in-depth interviews with a subsample of 25 heterosexual men and women. The low level of agreement found between the scores of the most widely used instruments for sexual function evaluation in epidemiology studies and self-diagnosis may be understood as a challenge for the predominant biomedical model and a need to re-conceptualize sexual dysfunctions other than as organic dysfunctions, with implications for both research and practice. Results show that individuals not only challenge illness concepts and sexual dysfunction diagnoses and their treatments, as they also construct sexual problems based on their impacts in daily life. Demonstrating the permanence of traditional social scripts that operate in the definitions of sexual function is one way to understand gender as an embodied social structure and get adequate practice to the problem, particularly in the Portuguese society where sexuality remains highly gendered.